Prognostic value of testosterone for the castration-resistant prostate cancer patients: a systematic review and meta-analysis - Miura, Noriyoshi; Mori, Keiichiro; Mostafaei, Hadi; Quhal, Fahad; Sari Motlagh, Reza; Abufaraj, Mohammad; Pradere, Benjamin; Aydh, Abdulmajeed; Laukhtina, Ekaterina; D'Andrea, David; Saika, Takashi; Shariat, Shahrokh F (International journal of clinical oncology, 2020)
INTRODUCTION: This systematic review and meta-analysis aimed to assess the prognostic value of testosterone in patients with castration-resistant prostate cancer (CRPC). MATERIALS AND METHODS: PubMed, Web of Science, and Scopus databases were systematically searched until December 2019, according to the Preferred Reporting Items for Systemic Review and Meta-analysis statement. The endpoints were progression-free survival (PFS) and overall survival (OS). RESULTS: We identified 11 articles with 4206 patients for systematic review and nine articles with 4136 patients for meta-analysis. Higher testosterone levels were significantly associated with better OS (pooled HR 0.74, 95% CI 0.58-0.95) and better PFS (pooled HR 0.51, 95% CI 0.30-0.87). Subgroup analyses based on the treatment type revealed that higher testosterone levels were significantly associated with better OS in CRPC patients treated with androgen receptor-targeted agents (ARTAs) (pooled HR 0.64, 95% CI 0.55-0.75), but not in those treated with chemotherapy (pooled HR 0.78, 95% CI 0.53-1.14). CONCLUSION: This meta-analysis demonstrated that the PFS and OS were significantly greater in patients with CRPC in those with higher testosterone levels than that of those with lower testosterone levels. In the subgroup analyses, lower testosterone levels were a consistently poor prognostic factor for OS in patients treated with ARTAs, but not in those treated with chemotherapy. Therefore, higher testosterone levels could be a useful biomarker to identify patient subgroups in which ARTAs should be preferentially recommended in the CRPC setting.
Keywords: Prostate cancer; mužské pohlaví; nádory prostaty rezistentní na kastraci; prognóza; Testosterone; Receptors, Androgen; Androgen receptor-targeted agents; Humans; Castration-resistant; Meta-analysis; androgenní receptory; Male; Prognosis; lidé; testosteron; Prostatic Neoplasms, Castration-Resistant